Complete Places Visioning - Collaborative and Problem-Based Learning in Urban Planning: Example of the Faculty of Architecture Poznan University of Technology in Poland - Kaźmierczak, Bartosz; Dominika Pazder, (European Journal of Social Science Education and Research, 2021)
Complete place visioning is an idea of designing active places in the city space. It is important part of urban design so as to act in accordance with inhabitants’ needs and provide vivid and socially desired places. In the paper there is presented an idea of complete places visioning introduced into academic learning system within the urban planning course at the Faculty of Architecture of Poznan University of Technology. The presented example of collaborative and problem oriented learning seems to be a useful tool in solving real urban problems and aiming at improving a quality of a city space. In the paper, collaboration is considered also in terms of participatory planning. There is shown the case study of polish commune Tarnowo Podgórne in which the project of civic activity centre together with neighboring public space is designed and realized as the final result of long-term collaboration between academic institutes and municipality.
Keywords: complete places visioning, problem-based learning, urban planning